A novel exergy-based assessment on a multi-production plant of power, heat and hydrogen: integration of solid oxide fuel cell, solid oxide electrolyzer cell and Rankine steam cycle. (11th February 2021) - Sadeghzadeh, Milad; Mehrpooya, Mehdi; Ansarinasab, Hojat
Title: Multi-production plant is an idea highlighting cost- and energy-saving purposes. However, just integrating different sub-systems is not desired and the output and performance based on evaluation criteria must be assessed. In this study, an integrated energy conversion system composed of solid oxide fuel cell (SOFC), solid oxide electrolyzer cell (SOEC) and Rankine steam cycle is proposed to develop a multi-production system of power, heat and hydrogen to alleviate energy dissipation and to preserve the environment by utilizing and extracting the most possible products from the available energy source. With this regard, natural gas and water are used to drive the SOEC and the Rankine steam cycle, respectively. The required heat and power demand of the electrolyzer are designed to be provided by the fuel cell and the Rankine cycle. The feasibility of the designed integrated system is evaluated through comprehensive exergy-based analysis. The technical performance of the system is evaluated through exergy assessment and it is obtained that the SOFC and the SOEC can achieve to the high exergy efficiency of 84.8% and 63.7%, respectively. The designed system provides 1.79 kg/h of hydrogen at 125 kPa. In addition, the effective designed variables on the performance of the designed integrated system are monitored to optimize the system's performance in terms of technical efficiency, cost-effectivity and environmental considerations. This assessment shows that 59.4 kW of the available exergy is destructed in the combustion chamber. Besides, the techno-economic analysis and exergoenvironmental assessment demonstrate the selected compressors should be re-designed to improve the cost-effectivity and decline the negative environmental impact of the designed integrated energy conversion system. In addition, it is calculated that the SOEC has the highest total cost and also the highest negative impact on the environment compared to other designed units in the proposed integrated energy conversion system.